The use of telehealth in the provision of after-hours palliative care services in rural and remote Australia: A scoping review. - Pathmavathy Namasivayam; Dung T Bui; Christine Low; Tony Barnett; Heather Bridgman; Pauline Marsh; Simone Lee (PLoS ONE)
Background Accessing quality palliative care, especially at the end of life is vital in reducing physical and emotional distress and optimising quality of life. For people living in rural and remote Australia, telehealth services can be effective in providing access to after-hours palliative care. Objective To review and map the available evidence on the use of telehealth in providing after-hours palliative care services in rural and remote Australia. Method Scoping review using Arksey and O'Malley methodological framework. Findings are reported in accordance with the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR). Scopus, Web of Science, CINAHL Complete, Embase via Ovid, Emcare via Ovid, and Medline via Ovid databases were searched. Peer-reviewed studies and grey literature published in English from 2000 to May 2021 were included. Results Twelve studies were included in the review. Four main themes were identified: 1) Stakeholder perceptions of service; 2) benefits to services and users; 3) service challenges; and 4) recommendations for service improvement. Conclusion Telehealth can connect patients and families with healthcare professionals and enable patients to continue receiving care at home. However, challenges relating to patients, service, staff skills, and experience need to be overcome to ensure the success and sustainability of this service. Improved communication and care coordination, better access to patient records, and ongoing healthcare professional education are required. Implications Protocols, comprehensive policy documents and standardized operating procedures to guide healthcare professionals to provide after-hours palliative care is needed. Ongoing education and training for staff is crucial in managing patients' symptoms. Existing service gaps need to be explored and alternative models of after-hours palliative care need to be tested.